Symbols And Mob Mentality in Short Story “The Lottery” By. Shirley Jackson - Aji, Galang Rambu; Rahayu, Endang Yuliani (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This study aims to discuss the symbolic components in Shirley Jackson's "The Lottery" and their significance in depicting mob mentality. The study examines symbols such as the black box, stones, and lottery ritual to illustrate how they reflect the townspeople's collective psyche as well as Jackson's indictment of societal conformity and blind tradition. Literary analysis approaches and symbolic interpretation frameworks serve as the key tools for this study.  Using semiotic and Jungian psychoanalysis, the study investigates the characters' behaviors and the villagers' subconscious within the context of primordialism. According to the research, conformity, peer pressure, and violence are key to mob mentality, which is motivated by a strong sense of tradition. These findings imply that valuing group identification and tradition over individual morality might result in detrimental practices around the world. Keywords: Mob Mentality, Jungian Psychoanalysis, Semiotics, Primordialism, Psychoanalysis